The journey to national independence of Nguyen Ai Quoc - Ho Chi Minh (1911-1945) - Dung, Vu Thi Hong (South Asian Journal of Social Sciences and Humanities, 2023)
Nguyen Ai Quoc - Ho Chi Minh is the founder of the Communist Party of Vietnam (early 1930), leader of the General Uprising in August 1945, to gain national independence, author of the Declaration of Independence declaring the establishment Democratic Republic of Vietnam (September 2, 1945) and the first President of the new Vietnam... He is the soul, the leader who leads and realizes the aspirations of independence and freedom of Vietnam. This study outlines the journey of national independence of Nguyen Ai Quoc - Ho Chi Minh in the period 1911-1945.